The State of the World's Children 2007 - United Nations Children's Fund (United Nations, 2007)
Millions of girls and women continue to live in poverty, disempowered and discriminated against. They are disproportionately affected by HIV/AIDS, less likely to attend school and often subject to physical and sexual violence. In most places, men continue to earn more pay than women for the same jobs. This year’s edition of UNICEF’s flagship publication, examines the status of women around the world. It concludes that an end to gender discrimination produces the ‘double dividend’ of benefiting women and children – which, in turn, has a positive impact on the health and development of societies everywhere.